The adsorption and decomposition of H2S on Ge(001): An STM study - McGovern, I; Ozer, H; Pethica, J; Egdell, R (2009)
The preparation of a nominal half-monolayer of sulphur on the Ge(001) surface via the adsorption of H2S and subsequent annealing has been monitored by STM. The 'saturated adsorption' surface image of dark-bright pairs is consistent with the dissociative adsorption of H and HS, respectively, on either atom of each Ge dimer. Images obtained at subsequent annealing stages show significant etching of the germanium surface, which is not detectable by electron spectroscopy. These STM images do not show evidence of the bridge-bonded sulphur that ideally results from this recipe. © 2009 The Surface Science Society of Japan.